On Some Values of the Sandor-Smarandache Function - Majumdar, AAK (GANIT: Journal of Bangladesh Mathematical Society, 2019)
Sandor [1] posed a new function, denoted by SS(n), and is defined as follows : being the binomial coefficients. This paper finds SS(n) for some particular cases of n. GANIT J. Bangladesh Math. Soc.Vol. 39 (2019) 15-25